Representasi Budaya Kawaii dalam Chara-Bentou - Hendy Reginald Cuaca Dharma (Bina Nusantara University, 2015)
This research aimed to find the inter-correlation between the factors of chara-bentou trend and the impression of kawaii culture on chara-bentou. By applying descriptive qualitative method, this study explained the factors of chara-bentou trend and the representation of kawaii in chara-bentou. Data were gathered from magazines, books, and questionnaire (field survey). Descriptive analysis was conducted to make interpretation based on the questionnaire given. As a conclusion, the children who have known chara-bentou since their childhood will know the art of food, like the Japanese said, “Eat with your eyes.”